Multiple shape memory effects of polyimide nanocomposites based on octa(aminophenyl) silsequioxanes - J. Yao; S. Ma; J. Zhang; Y. Wang; C. Wang; H. Zhou; C. Chen; G. Liu (eXPRESS Polymer Letters, 2021)
This work reports the synthesis of a series of shape memory polyimides by polycondensation of 2,2′-bis[4-(3-aminophenoxy)phenyl]hexafluoropropane (m-6FBAPP), 4,4′-(hexafluoroisopropylidene) (6FDA) and PA-terminated OAPS. The influence upon shape memory properties by the introduction of PA-terminated OAPS was investigated systematically in both experiments and simulations. PA-terminated OAPS acted as both a plasticizer and a rigid cage structure, preventing excessive movement of the polymer chain. Thus, both strain and shape recovery values of the resulting polyimide composites strongly depended on the content of PA-terminated OAPS. The shape memory polyimide composites showed high strain and recovery values equal to 247 and 94.3%, respectively. Additionally, these polyimide composites showed multiple shape memory effects and excellent shape memory cycle stability.